1995
DOI: 10.1007/bf00222203
|View full text |Cite
|
Sign up to set email alerts
|

Induction of diploid androgenetic and mitotic gynogenetic Nile tilapia (Oreochromis niloticus L.)

Abstract: Androgenesis is a potentially valuable technique for recovering fish from gene banks composed of cryopreserved sperm, developing inbred lines, and analyzing patterns of inheritance. The procedure for producing diploid organisms whose nuclear DNA is wholly of paternal origin is dependent on: (1) the denucleation of "host" eggs, and (2) the inhibition of the first mitotic division in order to double the haploid sperm chromosome complement following fertilization of host eggs. Denucleation of tilapia (Oreochromis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 14 publications
8
38
0
Order By: Relevance
“…Intra-species androgenesis conducted in this experiment also did not result in an increased survival rate of the offspring. A similar relationship between the time before the thermal shock (42°C, duration 4 min) was applied after fertilization was observed by Myers et al (1995) who conducted mitotic andro-and gynogenesis in Nile tilapia (Oreochromis niloticus). The authors found that the highest survival rate of andro-and gynogenetic offspring of Nile tilapia could be achieved when a thermal shock was applied 25 min (androgenesis) and 27.5 min (gynogenesis) after spermiation and with eggs incubated at 28°C.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Intra-species androgenesis conducted in this experiment also did not result in an increased survival rate of the offspring. A similar relationship between the time before the thermal shock (42°C, duration 4 min) was applied after fertilization was observed by Myers et al (1995) who conducted mitotic andro-and gynogenesis in Nile tilapia (Oreochromis niloticus). The authors found that the highest survival rate of andro-and gynogenetic offspring of Nile tilapia could be achieved when a thermal shock was applied 25 min (androgenesis) and 27.5 min (gynogenesis) after spermiation and with eggs incubated at 28°C.…”
Section: Discussionsupporting
confidence: 70%
“…A similar relationship was observed in this study for tench; this means that a thermal shock applied to stop the first mitotic division in inducing androgenetic development should be applied earlier than when gynogenetic development is induced. Meanwhile, Myers et al (1995) noted that the shock applied in order to duplicate genetic material in a diploid zygote should be earlier than in a haploid (andro-or gyno-genetic) zygote. The cause of the differences in the timing of the first division in a diploid zygote (androgenetic and gynogenetic) has not been identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These doses were higher than those recognized as optimum UV oocyte treatment for common carp (2500 J m ) by Lin and Dabrowski (1998), and were similar to those reported by Kucharczyk et al (1998) ). Viable UV doses for different species might result from differences in chorion structure, egg size and shape, as well as the position of the female pronucleus (Myers et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic (morphological) markers can be used if the trait is based on a recessive allele (Galbusera et al, 2000) and such characteristics have been used to assess inheritance in gynogenetic fish such as common carp (Nagy et al, 1978) and tilapia (Don and Avtalion, 1988;Varadaraj 1990;Myers et al, 1995). However, such morphological markers are rare (Ezaz et al, 2004a), and confirmation using biochemical or molecular markers is required to allow the unambiguous identification of inheritance.…”
Section: Introductionmentioning
confidence: 99%